2020
DOI: 10.1080/02673843.2020.1815550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep disorders among university students and its impact on academic performance

Abstract: Sleep disorders can have a critical effect on health and academic performance. This study aimed to estimate the prevalence and academic impact of various sleep disorders on university students by gender. This crosssectional study was conducted between May and September 2019. The prevalence of sleep disorders was assessed using the validated SLEEP-50 Questionnaire. Overall, 637 university students participated in the study (response rate: 100%); of these, 368 (57.8%) were female and 455 (71.4%) were > 20 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
3
16
0
1
Order By: Relevance
“…Feelings such as fear and social isolation, common in the pandemic context, can act to increase serum cortisol levels and reduce melatonin synthesis, resulting in changes in biological rhythms and dysregulation of the hypothalamic-pituitary-adrenal axis that result in changes in chronotype and perceptions of poor sleep (35,37) . This evidence is particularly noteworthy for the university population, which, even in pre-pandemic contexts, had a high prevalence of sleep disorders with serious repercussions on academic performance (38) .…”
Section: Factors Associated With the Perception Of Fear Of Covid-19 In University Studentsmentioning
confidence: 99%
“…Feelings such as fear and social isolation, common in the pandemic context, can act to increase serum cortisol levels and reduce melatonin synthesis, resulting in changes in biological rhythms and dysregulation of the hypothalamic-pituitary-adrenal axis that result in changes in chronotype and perceptions of poor sleep (35,37) . This evidence is particularly noteworthy for the university population, which, even in pre-pandemic contexts, had a high prevalence of sleep disorders with serious repercussions on academic performance (38) .…”
Section: Factors Associated With the Perception Of Fear Of Covid-19 In University Studentsmentioning
confidence: 99%
“…Studies based on questionnaires have shown the high prevalence of sleep disorders in many countries [8][9][10][11][12]. All around the world, these disorders cause negative effects on one's quality of life [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep and mental health have a bidirectional relationship, as sleep problems can be a symptom of mental health problems [ 17 ] and predispose to psychological illnesses like AX and Dep [ 18 ]. Sleep disorders are common among MSs due to heavy study load together with other stressors, and these disorders are associated with poor academic achievement [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%